PENGARUH EARNING PER SHARE, PRICE EARNING RATIO, RETURN ON EQUITY, DAN PRICE TO BOOK VALUE TERHADAP RETURN SAHAM - Firmansyah, Zaky Iqbal; Cahyono, Yuli Tri (Widya Balina, 2023)
The concept of stock return refers to the gains or profits obtained by investors from their investment in stocks, which may arise from both stock price appreciation and/or received dividends. This study aims to assess the impact of Earning Per Share, Price to Book Value, Price Earning Ratio, and Return on Equity on stock returns in companies listed in the LQ45 index on the Indonesia Stock Exchange (BEI) from 2020 to 2022. The samples studied were 72 companies that meet specified criteria. Multiple linear regression analysis is utilized as the analytical method. Empirical findings indicate that Earning Ratio (PER) significantly influences, while Earning Per Share (EPS), Return on Equity (ROE), and Price to Book Value (PBV) do not effect on stock returns.